2004
DOI: 10.21236/ada457868
|View full text |Cite
|
Sign up to set email alerts
|

Seeing-Is-Believing: Using Camera Phones for Human-Verifiable Authentication

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 13 publications
1
74
0
Order By: Relevance
“…Several recent studies have utilized barcode based out-of-band channels as security enhancement primitives. For example, McCune et al proposed the Seeing-is-believing (SiB) system [18] for human authentication. It also can be used for secure device pairing [19].…”
Section: Related Workmentioning
confidence: 99%
“…Several recent studies have utilized barcode based out-of-band channels as security enhancement primitives. For example, McCune et al proposed the Seeing-is-believing (SiB) system [18] for human authentication. It also can be used for secure device pairing [19].…”
Section: Related Workmentioning
confidence: 99%
“…While a cable provides no ambiguity about the device that is being paired [27], the majority of pairing approaches are wireless. These include infrared [29,2] and NFC, used by Bluetooth OOB pairing [17]; audio techniques where melodies [26] or synthesized speech are compared [11]; and visual approaches, where one of the two devices has a camera and it decodes either a 2D barcode [19] or flashing LED [23] on the other device. Others are more physical, involving synchronized button pressing [25] or shaking of the devices [14,18].…”
Section: Device Pairingmentioning
confidence: 99%
“…Other researchers have investigated pairing approaches that use flashing lights. Saxena [23] found that a flashing LED on one device, paired with a camera on the other, would be a performant alternative to approaches that required screens showing barcode representations of public keys [19]. Systems for data transmission subsequent to pairing have also been developed to make use of flashing lights: LedTX [24] provides data transfer from a UbiLighter instrumented lighter, with a flashing LED on the lighter decoded by a Javascript program accessing a laptop's webcam; FlashLight [13] creates a bidirectional communication channel between a tabletop and mobile phone, using the built-in cameras and displays of the devices.…”
Section: Device Pairingmentioning
confidence: 99%
“…Moreover, the use of evolutionary algorithms are almost non-present for this purpose. Some of the relevant work on user authentication system has been reported in [3], [9] and [8]. However only [10] has done some preliminary work using GA. To the best of our knowledge no previous study has used any of the genetic algorithms for user authentication on smart phones.…”
Section: Related Workmentioning
confidence: 99%